Sadi Carnot: uma breve discussão sobre sua contribuição para o aperfeiçoamento das máquinas a vapor e para o desenvolvimento da Termodinâmica - Nascimento, José Rodrigues do (2023)
The investigations of some scientists usually gain notoriety in History, when their studies are associated with relevant contributions to Science. However, this is not the rule and, in some cases, as a result of precarious, superficial or even non-existent analyses, their names are omitted from textbooks and scientific texts. The most emblematic example is the relationship between Sadi Carnot and Thermodynamics. Despite all his contribution to the formation of this new branch of study, his name is silenced or discreetly mentioned in most textbooks and scientific texts, when discussing the historical formation of this branch of study of Physics. Therefore, this study aims to discuss the legacy of the French engineer Sadi Carnot, regarding his contributions to the improvement of steam engines and to the development of the initial scientific concepts of Thermodynamics. To meet this goal, methodologically, a qualitative research with a historiographical approach was carried out. In this sense, we chose to emphasize relevant primary and secondary sources, aiming to be as consistent as possible with the achievements and historical facts experienced by the engineer mentioned above. Sadi Carnot was a contemporary of the Industrial Revolution, started by England, and was influenced by the French Revolution, both of which occurred in the 18th century, bringing radical changes to the society in which he lived and to future generations. Heir to a scientific tradition and guided by patriotic feelings, he began to study how steam engines worked, in order to collaborate with his country, given the industrial and military advance. As a result of this action, at the age of 28, he published his book Réflexions sur la puissance motrice du feu et sur les machines propres à developper cette puissssance (Reflections on the motive power of fire and on the machines suited to the development of this power), considered by many authors to be a masterpiece of engineering and science, which did not have much adherence at the time of its publication, for being too advanced in relation to the innovative scientific concepts it discussed. As a contribution to steam engines and the initial concepts of Thermodynamics, Carnot left as his legacy, in this pioneering study that sought to understand and explain the theory of fire engines: the Carnot cycle, the Carnot theorem, the Carnot efficiency and the basic foundational postulates of the first and second law of Thermodynamics.